Carboxyl-functionalized mesoporous silica nanoparticles for the controlled delivery of poorly water-soluble non-steroidal anti-inflammatory drugs. (15th October 2021) - Gou, Kaijun; Wang, Yumei; Guo, Xianmou; Wang, Yuxin; Bian, Yan; Zhao, Haiqing; Guo, Yingyu; Pang, Yue; Xie, Linlin; Li, Sanming; Li, Heran
Abstract: The purpose of this study was to investigate the delivery of poorly water-soluble non-steroidal anti-inflammatory drugs (NSAIDs) by carboxyl-functionalized mesoporous silica nanoparticles (MSN-COOH) with high specific surface area (SBET ). In this study, MSN-COOH was prepared by collaborative self-assembly using cetyltrimethylammonium bromide (CTAB) as template and hydrolysis (3-triethoxyl-propyl) succinic anhydride (TESPSA) as co-structure auxiliary directing agent (CSDA). The drug delivery systems were constructed with NSAIDs including Nimesulide (NMS) and Indomethacin (IMC) as model drugs. Moreover, the characterization techniques, hemolysis and bio-adsorption testes, in vitro drug release and in vivo biological studies of MSN-COOH were also carried out. The characterization results showed that MSN-COOH is spheres with clearly visible irregular honeycomb nanopores and rough surface (SBET : 1257 m 2 /g, pore volume (VP ): 1.17 cm 3 /g). After loading NMS/IMC into MSN-COOH with high drug loading efficiency (NMS: 98.7 and IMC: 98.2%), most crystalline NMS and IMC converted to amorphous phase confirmed using differential scanning calorimeter (DSC) and X-ray power diffraction (XRD) analysis. Meanwhile, MSN-COOH significantly increased the dissolution of NMS and IMC compared with non-functionalized mesoporous silica nanoparticles (MSN), which was also confirmed by wettability experiments. The results of in vivo biological effects showed that MSN-COOH had higher bioavailability of NMS and IMC than MSN, and exerted strong anti-inflammatory effects by delivering more NMS and IMC in vivo . Statement of significance: This study successfully prepared MSNs-COOH (mesoporous silica nanoparticles modified with negatively charged carboxyl groups on the surface and in the pores) with high specific surface area and pore volume by using the negatively charged carboxyl group (hyd-TESPSA) and the positively charged CTAB self-assembled through electrostatic attraction under alkaline conditions. The drug delivery systems were constructed with Nimesulide (NMS) and Indomethacin (IMC) as model drugs. The results showed MSNs-COOH had high drug loading capacity and also exhibited good in vitro drug release properties. Interestingly, NMS loaded MSNs-COOH also had a potential pH responsive release effect. In vivo biological studies revealed that NMS/IMC loaded MSNs-COOH could evidently improve the bioavailability and played the strong anti-inflammatory effects. Graphical abstract: Image, graphical abstract